CHARACTERISTICS OF CALCULATING INSURANCE TARIFFS IN INSURING THE ACTIVITIES OF BUSINESS SUBJECTS - Mamadjanov, Sh. (PT. Antis International Publisher, 2024)
Objective: The study aims to investigate the effectiveness of actuarial calculations in determining insurance rates for business entities, emphasizing the need for flexibility across various types of insurance and adapting to specific risks and social conditions. Methods: The research employs actuarial techniques based on mathematical statistics and probability theory to assess risks, set tariffs, and calculate insurance payments. It includes determining damage frequency and severity within different risk groups, while accounting for the cost of insurance services and business entity property. Results: The study finds that insurance payments depend on the actual value of lost property or restoration costs in case of partial damage. In cases where the property value exceeds the insurance amount, the business entity must cover the difference. The analysis also reveals that actuarial calculations must adapt to regional and industry-specific risks, with social and economic factors influencing the outcomes. Novelty: This research introduces a flexible system of actuarial calculations that incorporates both planned and reported actuarial methods. It highlights the need for new incentive mechanisms, such as preferential tariffs for regular business entities, to increase interest in insurance services and ensure adequate protection in rapidly changing economic environments.